"Power rule" is the one rule among the following choices given in the question that <span>would apply to the expression w^2w^3. The correct option among all the options that are given in the question is the second option or option "B". I hope that this is the answer that has actually come to your desired help.</span>
7√7
using the ' rule of radicals '
• √a × √b ⇔ √ab
simplifying the radicals
√28 = √(4 × 7 ) = √4 × √7 = 2√7
√63 = √(9 × 7) =√9 × √7 = 3√7
√112 = √(16 × 7 ) = √16 × √7 = 4√7
substituting into the expression
3(2√7) - 5(3√7) + 4(4√7) = 6√7 - 15√7 + 16√7 = 7√7
Answer:
x-4
Step-by-step explanation:
6x+6-5x-10=
x-4
( you have to multiply what is inside the parenthases to get to the first step that i did)